Cause and Clinical Profile of 379 cases of Ocular Trauma - Jeyanth Rose; Renu Raju (Delhi Journal of Ophthalmology)
Background: Ocular trauma is a major cause of monocular blindness and visual impairment throughout the world. Population based epidemiological studies in south India have found prevalence rates of 2-10%. The aim of our study was to find the demographic and clinical profile of patients with ocular trauma. Materials and methods: All patients who came to our emergency services between July 2004 and January 2005, with history of ocular trauma or foreign body in either eye, within 2 weeks of the date of presentation were included in this prospective, cross sectional survey and underwent a complete eye examination including best corrected visual acuity, slit lamp examination and fundoscopy. Results: Age distribution of ocular trauma showed gradual decline with age with maximum number of patients in the 0-10 year age group. Temporal spectrum showed a bimodal peak in January and November. Male predomination accounted for 71 % of patients. Work related trauma accounted only for 22.4% of patients. The “stick” predominated as the premier object of insult (22.2%), Vegetative matter 10.4%. Road Traffic Accidents 9.4% and Metal 8.2%. Chemical injuries accounted for 7.7% and Open globe injuries 19.3% of patients. Conclusions: The demographic factors associated with an increased incidence of ocular trauma include young age, male sex and festive seasons of the calendar year including November and January. The “stick” was the most common object of insult. Clinical profile showed a high incidence of open globe injuries(19.3%). This study highlights some differences in the profile of ocular trauma as seen in a developing country. The predominant occupation in rural India is agriculture and the premier form of fuel used in most households for cooking is firewood. Thus the results of a high percentage of ocular trauma related to sticks and vegetative matter. Chemical injuries which accounted for 7.7% of patients with ocular trauma and were predominantly related to the local practicesof “pan” chewing. The high percentage of open globe injuries is indicative of the severity of ocular trauma seen in rural India.